2019
DOI: 10.3389/fimmu.2019.01322
|View full text |Cite
|
Sign up to set email alerts
|

CXCR5+ CD8 T Cells: Protective or Pathogenic?

Abstract: CD8 T cells are infrequently considered part of germinal center reactions. Yet, a distinct CXCR5+ CD8 T cell subset identified within the B cell follicle and germinal center in situations of chronic antigen has recently been defined. CXCR5+ CD8 T cells maintain transcriptional and phenotypic features consistent with the CD8 T cell nomenclature of a non-exhausted, effector memory population. CD8 T cell localization to the B cell follicle suggests a functional profile similar to CD4 T follicular helper cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 57 publications
(193 reference statements)
0
39
1
3
Order By: Relevance
“…Corresponding to the previous studies in circumstances of viral infection and tumor infiltration, we confirm the selfrenewal and effector memory-like phenotype of CXCR5 + CD8 + T cells in MIBC. 17,26 Intriguingly, we discovered that CXCR5 + CD8 + T cells expressed activated TCF1 (transcripted by TCF7) compared to its CXCR5 − CD8 + T cells counterpart. Meanwhile, it is reported that TCF7 + identified a subset of superior survival-indicating CD8 + T cells in melanoma, 36 which is consistent with our results.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Corresponding to the previous studies in circumstances of viral infection and tumor infiltration, we confirm the selfrenewal and effector memory-like phenotype of CXCR5 + CD8 + T cells in MIBC. 17,26 Intriguingly, we discovered that CXCR5 + CD8 + T cells expressed activated TCF1 (transcripted by TCF7) compared to its CXCR5 − CD8 + T cells counterpart. Meanwhile, it is reported that TCF7 + identified a subset of superior survival-indicating CD8 + T cells in melanoma, 36 which is consistent with our results.…”
Section: Discussionmentioning
confidence: 93%
“…In the TCGA Cohort, the CXCR5 + CD8 + T signature score was comprised of the mean value of the mRNA expression of CD8A, CXCR5, CXCR3, ICOS, CD27, IL21, TNF, TNFRSF6B, PDCD1, TBX21, SLAMF6, and IL27RA. 17,26 To control the range of the CXCR5 + CD8 + T signature score, the mRNA expression was pre-calculated with log 2 (x + 1). The gene constitution of multiple signatures was provided in Supplementary Table 3.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR5, which is expressed in Tfh cells, mature B cells, and Treg cells, is involved in B cell migration and the formation of germinal cells (GCs) and guides disease-causing double negative (DN) T cells into lymphoid organs and kidneys ( 43 ). In CXCR5-deficient lupus murine model, the migration of DN T cell to lymph nodes was reduced and the kidney was not infiltrated ( 44 ).…”
Section: Targeting B Cellsmentioning
confidence: 99%
“…Several studies have demonstrated a population of CXCR5 + CD8+ T cells within B cell follicles. These cells have been shown to have different transcriptional profiles from their CXR5-CD8+ T cell counterparts and their role in controlling viral replication has been the subject of many recent studies (70, 71). It has been shown that increased CXCR5+ effector CD8+ T cells in secondary lymphoid tissue is associated with increased control of chronic viral infections, including HIV (66, 72, 73).…”
Section: Introductionmentioning
confidence: 99%